Consumption of Green Tea Protects Murine Haematopoiesis from Drug-Induced Myelosuppression - Sarkar, Biswajyoti; Nath, Supriya; Roy, Kamalika; Ghosh, Sanhita; Paul, Sharmistha; Hussain, Aabid; Karan, Mintu; Pal, Chiranjib (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Objectives: Tea is a globally favored beverage. Protective effects of tea are already reported for bacterial infection, several forms of cancer, and against chemotherapeutic agents; however, effects of tea decoctions (as per human consumption) on the lineage differentiation and chemoprotection of the bone marrow haematopoietic stem cells (HSCs) are not widely known. The present work aimed to appraise the possible effect of green and black tea decoctions (prepared as per human consumption) on the lineage differentiation of the HSCs and any protective effect against cellular suppression. Methods: Tea decoctions (simulating human consumption, i.e., 2.5 gm. in 100 ml) were prepared with certified organic green and black tea leaves. Cyclophosphamide (80 mg/kg/day; 100 µl/mice) was given as required. BALB/c mice were divided into six groups: Naïve; only cyclophosphamide – treated; groups gavage-fed with only green tea and black tea decoctions; and tea-decoction fed and cyclophosphamide-treated groups. Bone marrow cells were collected, divided, and utilized for further experiments after the experimental period. Results: The tea decoctions protected the granulocyte-monocyte progenitors against cyclophosphamide-induced cellular suppression but did not induce HSC proliferation. Further investigation revealed that green tea decoction was more effective in providing myeloprotection by inhibiting the overproduction of reactive oxygen species (ROS), induction of DNA repair enzymes and drug-metabolizing enzymes Cytochrome P450 1a2 (Cyp1a2) and Cyp2b10, and ameliorating the Toll-like receptor 4 (TLR4)-mediated cell-detrimental increase of cytokines. Conclusions: Taken together, green tea decoction was effective in protecting cyclophosphamide-induced myelosuppression in murine bone marrow HSCs at human consumption doses.